THE CONFORMITY BETWEEN LAW NO. 1 OF 2021 AND LAW NO. 30 OF 1999 IN THE RESOLUTION OF ECONOMIC DISPUTES BETWEEN INDONESIA AND EFTA COUNTRIES (Universitas Suryakancana, 2022)
Law No. 1 of 2021 mentions that there are basic materials stipulated in the IE-CEPA Agreement, among others, dispute resolution. This paper aims to explain the implementation of economic dispute resolution in the approval of a comprehensive economic partnership between Indonesia and EFTA countries perspective of the Arbitration Law. This research uses a library approach, where the data collection technique uses literature and document studies. Meanwhile, the data analysis used is a triangulation technique. The results showed that the approval of a comprehensive economic partnership between Indonesia and the EFTA country as stipulated in Law No. 1 of 2021 does not clash with Law No. 30 of 1999 on Arbitration. This is because there is an accompanying Arbitration Event Law, especially concerning the selection of arbitration panels. In all, there are 8 (eight) perspectives that show the similarity of the two Laws, namely: Written application in choosing dispute resolution through Arbitration; Conciliation and Mediation; Selection of arbitrators; Examination by the Arbitrator; Language of Arbitration; Determination is final and binding; Peaceful efforts; And not willing a person to be elected as an arbitrator.Keywords: Arbitration, Disputes, EFTA.